O-103BRONCHIOLITIS OBLITERANS SYNDROME IN LIVING-DONOR LOBAR LUNG TRANSPLANTATION. (June 2014) - Miyamoto, Ei; Chen, F.; Yamada, T.; Sato, M.; Aoyama, A.; Date, H.
Abstract : Objectives: Bronchiolitis obliterans syndrome (BOS) is the main cause of late morbidity and mortality in lung transplantation and defined as the presence of a persistent fall in forced expiratory volume in 1 second associated with an obstructive ventilator defect. However, few studies have been reported concerning BOS after living-donor lobar lung transplantation (LDLLT). The aim of this study was to determine the prevalence and outcome of BOS in LDLLT. Methods: Clinical records, pulmonary function data and radiologic findings of 42 patients who underwent LDLLT at our institution between June 2008 and December 2013 were examined. Computed tomography, pulmonary function test and ventilation-perfusion scan were performed prospectively at 3, 6 and 12 months after LDLLT  and annually from then on. Results: There were 18 males and 24 females with a median age of 44 years (6-64). Single LDLLT was performed in 8 patients, while bilateral LDLLT was conducted in 34 patients. The median follow-up period was 24 months (1-70). Conditions leading to lung transplantation were mainly idiopathic interstitial pneumonia (35.6%) and bronchiolitis obliterans after hematopoietic stem cell transplantation (31.1%). Seven patients were diagnosed with BOS (6 patients in BOS stage 1 and 1 in potential BOS stage) based on the decrease of forced expiratory volume in 1 second. The patients showed air trapping in ventilation-perfusion scan. In these patients, azithromycin was effective to improve or hold forced expiratory volume in 1 second. Five-year BOS free rate was 66.8%. Five-year overall survival was 80.0%. Conclusions: BOS was confirmed in 7 LDLLT patients (16.7%) with good response to azithromycin. Ventilation-perfusion scan might be useful for the diagnosis of BOS after LDLLT. Disclosure: No significant relationships.